A RISK ADJUSTED CAPITATION REGIME FOR COMMUNITY BASED SOCIAL HEALTH INSURANCE PROGRAMME - Ajijola, L A; Ojikutu, R K; Adeleke, I A (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2018)
The general poor state of Nigeria’s healthcare services informed the need for the establishment of the National Health Insurance Scheme (NHIS). Health care providers reimbursing systems under the scheme include among others reimbursement method, capitation and fee-for-service with capitation specifically being used under Community Based Social Health Insurance Programme (CBSHIP). This study applies a risk adjustment model on managed care organizations with the goal of attaining a fair and adequate reimbursement. The risk-based reimbursements reflect cost differences attributable to the enrolees. Using enrolees data of 23,375 individuals, results show that a sum of N528, 546.52 ($1,679.26) will be saved by the scheme and cream-skimming of members by health status and plans due to morbidity risk will be neutralized.